Camp Chase and the evolution of Union prison policy - Pickenpaugh, Roger (Univ. of Alabama Press, 2007)
Training camp -- Improvised prison camp -- Parole camp - -- Exchange and escape -- The search for stability -- The lives of the prisoners -- The health of the prisoners -- "I think I feel a change" -- Afterword : keeping alive the memory